POTENSI ALELOKIMIA DARI EXTRACT DAN MULSA BIOMAS TANAMAN SORGUM (Sorghum bicolor L. Moench) - Advent F. Sitanggang; Marulak Simarmata; Bilman Wilman Simanihuruk; Uswatun Nurjanah (BPFP Universitas Bengkulu, 2021)
[ALLELOCHEMICAL POTENTIAL OF AQUEOUS EXTRACT AND MULCH OF PLANT BIOMASS OF SORGHUM (Sorgum bicolor L. Moench)]. This study was aimed to examine the allelopathic potential of sorghum through aqueous extract and mulch from biomass on seed germination and early growth of three tested plants, namely rice, mustard and cucumber. The results showed that the aqueous extract of the sorghum biomass significantly inhibited the germination of mustard and cucumber seeds, reduced the vigor-index of the germination of rice, mustard and cucumber seeds, and suppressed the growth of radicle length of mustard sprouts. The same thing was seen when sorghum biomass was tested as mulch which also suppressed the early growth of the tested plants on the variables of stem height, fresh and dry weight of biomass of rice, mustard and cucumber. The higher the concentration of allelochemicals extract or sorghum mulch, the stronger the inhibition on germination and early growth of the three test plants. At a concentration of 10% allelochemicals suppressed the germination of mustard and cucumber to 76 and 79%, respectively, while a dose of 10% mulch suppressed early growth in the height of rice, mustard, and cucumber to 56, 55, and 68%; and dry weight to 53, 30 and 60%. The results of this study are important information about the allelochemical potential of sorghum as a natural herbicide in integrated weed management